Examining the Potential Influence of Violence Exposure on the Link Between Callous-Unemotional Traits and Delinquent and Aggressive Behavior in Children and Adolescents - Joyner-Carpanini, Bridget (Crime & delinquency, 2023)
Callous-unemotional traits have been consistently tied to non-violent and violent criminal involvement among adolescents and adults. However, research has yet to fully explore potential underlying mechanisms that explain how and why these associations exist. The current study addresses this gap by analyzing data drawn from the National Survey of Child and Adolescent Well-Being I (NSCAW I) to examine violence exposure as a potential moderator to the association between callous-unemotional traits and delinquent and aggressive behaviors. Our analyses revealed that callous-unemotional traits were significantly associated with both delinquent and aggressive behaviors. However, we found no evidence to suggest that violence exposure moderates this association. We conclude by discussing the implications of our study for future research.